2003
DOI: 10.1046/j.1471-4159.2003.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 nucleotide receptor activation enhances IFNγ‐induced type II nitric oxide synthase activity in BV‐2 microglial cells

Abstract: Under normal and pathological conditions, brain cells release nucleotides that regulate a wide range of cellular responses due to activation of P2 nucleotide receptors. In this study, the effect of extracellular nucleotides on IFNc-induced NO release in murine BV-2 microglial cells was investigated. BV-2 cells expressed mRNA for metabotropic P2Y and ionotropic P2X receptors. Among the P2 receptor agonists tested, ATP, ADP, 2¢,3¢-O-(4-benzoylbenzoyl)-ATP (BzATP), and 2-methylthio-ATP (2-MeSATP), but not UTP, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 79 publications
4
48
0
Order By: Relevance
“…In addition, P2X7 receptor activation by ATP potentiated IFNγ-induced NO production in microglia [35]. Similarly, we observed a reduction in NO and ROS production in peritoneal macrophages from P2X7 KO mice compared to WT mice, suggesting an inefficient innate immune response in the inflammatory environment of P2X7 KO mice (unpublished data).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, P2X7 receptor activation by ATP potentiated IFNγ-induced NO production in microglia [35]. Similarly, we observed a reduction in NO and ROS production in peritoneal macrophages from P2X7 KO mice compared to WT mice, suggesting an inefficient innate immune response in the inflammatory environment of P2X7 KO mice (unpublished data).…”
Section: Discussionsupporting
confidence: 68%
“…In astrocytes, binding of BzATP has been linked to several cell-signaling pathways including ERK1 and 2 and p38 MAP kinase (Gendron et al, 2003b), as well as the transcriptional complexes AP-1 (Panenka et al, 2001) and NF-κB (Ferrari et al, 1997). BzATP has also been shown to enhance IL-1β-induced activation of NF-κB and AP-1 (John et al, 2001;Panenka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular nucleotides have been shown to increase IL-1β activation of the transcription factors AP-1 and NF-κB, which would be expected to enhance activation of NOS2 (Ferrari et al, 1997;John et al, 2001). Indeed, blockade of purinergic receptors with oATP has been shown to decrease macrophage production of NO in response to lipopolysaccharide (Hu et al, 1998), and more recently it has been demonstrated that BzATP can enhance production of NO induced by IFN-γ in a microglial cell line (Gendron et al, 2003b). Given the above effects of BzATP, we examined the impact of P2X 7 R activation on NOS2 induction (Fig.…”
Section: Bzatp Enhances No Production Induced By Il-1β/ifnγmentioning
confidence: 99%
“…It has also been implicated in the activation and maturation of T cells (10,11), the formation of giant cells (12,13), the killing of invading microorganisms in macrophages (14 -16), the activation of the inducible form of NO synthase (17,18), and the shedding of L-selectin (CD62L) (19,20), an adhesion molecule that functions in leukocyte binding to the activated endothelium and in lymphocyte homing to high endothelial venules.…”
mentioning
confidence: 99%